Germ Warfare and the Zero-Sum Game - Abd Razak, Dzulkifli (1995)
AS IF THE USE OF TOXIC CHEMCALS and deadly bombs are not enough to bring destruction, some nations are busying themselves with another frontier of warfare the use deadly germs as biological weapons. While there is as yet no report of largescale use of germs as weapons, lately, there is evidences to indicate that germs warfare did take place towards the end of World War Two. Biological warfare is banned under the Geneva Protocol of 1925. Theoretically, germs can be used as war weapons. Such microorganisms can be used to infect human beings, gradually poisoning them. For example, the bacteria Clostridium botulinum, a causative agent in food poisoning by secreting the deadly botulinus toxin, can cause severe respiratory depression and death.